PRELIMINARY STUDY OF THE RELATIONSHIP BETWEEN CHEMISTRY LEARNING MOTIVATION AND SELF-REGULATION OF STUDENTS - Elmafiza Indillah; Fithrah Auliya; Fitri Damayanti; Muntholib Muntholib; Aulin Risyda Risyda (Jurnal Pembelajaran Sains, 2022)
Chemistry is a science that seeks answers to questions about what, why, and how a natural phenomenon is closely related to a substance's composition, structure, and properties. This study aims to determine the level of learning motivation of students of SMA Islam Sabilurrosyad in Chemistry subject, the level of student self-regulation, and the relationship between learning motivation and student self-regulation. This non-experimental study used a quantitative correlational method, namely the Pearson correlation analysis technique or Product Moment correlation. The study results showed that most students learning motivation and self-regulation levels were in the moderate category, namely 66.67% of respondents who understood motivation and 63.89% who understood self-regulation. In addition, data processing using SPSS found a relationship between learning motivation and self-regulation.